2006
DOI: 10.2139/ssrn.925650
|View full text |Cite
|
Sign up to set email alerts
|

Inside the Family Firm: The Role of Families in Succession Decisions and Performance

Abstract: This paper uses a unique dataset from Denmark to investigate the impact of family characteristics in corporate decision making and the consequences of these decisions on firm performance. We focus on the decision to appoint either a family or external chief executive officer (CEO). The paper uses variation in CEO succession decisions that result from the gender of a departing CEO's firstborn child. This is a plausible instrumental variable (IV), as male first-child firms are more likely to pass on control to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
426
7
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(461 citation statements)
references
References 41 publications
20
426
7
8
Order By: Relevance
“…Several studies have shown that family firm characteristics, and here especially the active involvement of a family member, or generational issues may have an important impact on firm performance 11 and policy (e.g. Pérez-González (2006), Villalonga and Amit (2006) or Bennedsen et al (2007)). Considering these findings, founding family firms have further been categorised into groups depending on the active position and generation of a family member.…”
Section: Ownership Variablesmentioning
confidence: 99%
“…Several studies have shown that family firm characteristics, and here especially the active involvement of a family member, or generational issues may have an important impact on firm performance 11 and policy (e.g. Pérez-González (2006), Villalonga and Amit (2006) or Bennedsen et al (2007)). Considering these findings, founding family firms have further been categorised into groups depending on the active position and generation of a family member.…”
Section: Ownership Variablesmentioning
confidence: 99%
“…Bloom and Van Reenen (2006) found that mismanagement will occur in particular if a business is transferred to the eldest son (primogeniture), whereas the management abilities will not be affected if the entire family appoints the management of a transferred business. In contrast, Morck, Shleifer, and Vishny (1989), Bennedsen, Nielsen, Pérez-González and Wolfenzon (2007), Pérez-González (2006) and Villalonga and Amit (2006) discovered in general a significantly poorer performance of companies run by heirs compared to firms with non-family executives. Grossmann and Strulik (2010) disapproved an inheritance tax privilege for businesses in a general equilibrium model.…”
Section: Pros and Cons For An Inheritance Tax Privilege For Businessesmentioning
confidence: 75%
“…Inheritance tax can jeopardize businesses due to liquidity problems if the transferees of a business lack liquid assets to meet inheritance tax liability and if, in addition, imperfect capital markets inhibit refunding. Furthermore, advocates of an inheritance tax privilege for businesses stress the specialized leading skills of relatives resulting from their particular identification and family-specific know-how (Bennedsen, Nielsen, Pérez-González, and Wolfenzon 2007). Additionally, it is stated that principal-agent problems are less virulent.…”
Section: Pros and Cons For An Inheritance Tax Privilege For Businessesmentioning
confidence: 99%
“…By selecting the CEO from the small pool of family heirs, the firm might have a top executive who lacks managerial talent. Consistent with this view, Pérez-González (2006) and Bennedsen et al (2007) find evidence of lower operating performance of firms which experienced a family succession. The success of large acquisitions strongly depends on the managerial skills of those who conduct them, for instance highly-skilled CEOs may have abilities to detect good targets.…”
Section: Propensity To Engage In Acquisitionsmentioning
confidence: 82%